2019
DOI: 10.1186/s13104-019-4154-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of loss to follow-up among HIV infected adults after initiation of first line anti-retroviral therapy at University of Gondar comprehensive specialized Hospital Northwest Ethiopia, 2018: retrospective follow up study

Abstract: Objectives The aim of this study was to estimate the incidence of lost to follow up from anti-retroviral therapy (ART) care and identify the associated factors among human immunodeficiency virus (HIV) infected patients after first-line ART initiation at University of Gondar comprehensive specialized hospital, Northwest Ethiopia between January 2012 and January 2018. Results The overall incidence rate of lost to follow up was 12.26 per 100 person years (95% CI (10.61–14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
55
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(94 citation statements)
references
References 31 publications
23
55
3
Order By: Relevance
“…Our study has shown that among the key populations people who inject drugs are predominantly LTFU due to their chaotic behaviours, compromised mental state, and absence of family support. This finding has been supported by Mekonnen et al in his study (17). Our study findings reveal a significant association between LTFU and PLHIV with undisclosed identity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study has shown that among the key populations people who inject drugs are predominantly LTFU due to their chaotic behaviours, compromised mental state, and absence of family support. This finding has been supported by Mekonnen et al in his study (17). Our study findings reveal a significant association between LTFU and PLHIV with undisclosed identity.…”
Section: Discussionsupporting
confidence: 91%
“…National evidence reveals that some of the factors contributing to LTFU include disease associated stigma and discrimination, attitude of healthcare staff, timings of healthcare facilities, catastrophic out of pocket health spending, and weak social support systems (16) In our study we observed that young age and male gender are strong risk factors for LTFU in patients on ART. This finding has also been observed in other studies conducted in Guinea-Bissau, Ethiopia, Kenya, Nigeria and parts of West Africa (12,(17)(18)(19)(20). Pakistan has a male dominated society with strong socio-cultural norms.…”
Section: Discussionsupporting
confidence: 85%
“…Three papers indicated that economic constraints such as being dependent patients for source of food and daily laborers were risk factors for treatment interruption [10,49,51]. Being a merchant, farmer, daily labour and jobless had a greater risk of dropout [38,41]. On the other hand, one study reported that merchants were at higher risk of death [45] However, except Assesfa et al [12] 334, 819…”
Section: Factors Related To Patient Retention and Attrition Socio-demmentioning
confidence: 99%
“…Mental health issues such as taking hard drugs (cocaine, cannabis and IV drugs) and excessive alcohol drinking were risk factors for treatment defaulting [52]. Any types of substance use was reported as risk for loss to follow up [38]. It was also reported that patients with higher score for stress were poor in ART adherence [57].…”
Section: Total Number Of Participants 546250mentioning
confidence: 99%
“…Different studies showed that LTFU is associated with base line sociodemographic factors like sex [10,16,[22][23][24], age [10,11,13,25,26], educational status [26,27], marital status [25,28,29], occupation [30,31], disclosure status [16,27], distance from the health facility [29], caregiver [32,33] and clinical and treatment related factors like baseline WHO stage [25,34], baseline CD4 count [13,31,35], history of opportunistic infection at enrollment [10], baseline functional status [15,32,[35][36][37], opportunistic prophylaxis [11,13,14,29] and type of ART regimen at start of their medication [23,31].…”
Section: Introductionmentioning
confidence: 99%